2004
DOI: 10.1111/j.1467-6281.2004.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Type of Accounting Standards on Preparers’ Judgments

Abstract: This article examines preparers' consolidation judgments and how they are impacted by the precision of accounting standards (substance-overform versus rules-based). The examination is performed via two laboratory experiments in a consolidated accounting setting. In Experiment 1 it was found that when subjects used a substance-over-form accounting standard they justified their consolidation judgments on case specific information rather than on different interpretations of the phrase 'capacity to control'. In Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 17 publications
3
47
0
6
Order By: Relevance
“…In the model adjusted by stepwise, the years 2011 and 2012 had a significantly higher average comparability when compared to 2004. The results found corroborate other researches addressing the quality of accounting information (Collins, Pasewark, & Riley, 2012;Psaros & Trotman, 2004;Agoglia, Doupnik, & Tsakumis, 2011) and prove the superiority of the principle-based standard also over the comparability of financial reports. The main conclusion of this research is that increasing manager's discretionary power through flexibility of accounting standards does not decrease the comparability of financial reports.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…In the model adjusted by stepwise, the years 2011 and 2012 had a significantly higher average comparability when compared to 2004. The results found corroborate other researches addressing the quality of accounting information (Collins, Pasewark, & Riley, 2012;Psaros & Trotman, 2004;Agoglia, Doupnik, & Tsakumis, 2011) and prove the superiority of the principle-based standard also over the comparability of financial reports. The main conclusion of this research is that increasing manager's discretionary power through flexibility of accounting standards does not decrease the comparability of financial reports.…”
Section: Introductionsupporting
confidence: 80%
“…According to the authors, their findings contradict the arguments that inaccurate standards taking into account the substance under the form makes them less effective to fight biases in financial reports when compared to rule-based standards. Corroborating the findings of Psaros and Trotman (2004), Agoglia et al (2011) observed in their experiments that financial directors subject to a more flexible regulatory system are less exposed to aggressive practices in financial reporting than financial directors in stricter systems. Overall, based on these studies, we notice the existence of a proven superiority of the standard based on principles over the standard based on rules.…”
Section: Figurementioning
confidence: 62%
See 3 more Smart Citations